Early markers of pathological left ventricular remodeling in patients after ST-elevation myocardial infarction according to speckle-tracking echocardiography - V. E. Oleinikov; A. V. Golubeva; V. A. Galimskaya; A. V. Babina; N. A. Donetskaya (Российский кардиологический журнал)
Aim. To assess early predictors of pathological remodeling in patients after ST-elevation myocardial infarction (STEMI) using speckle-tracking echocardiography (STE).Material and methods. The study included 114 STEMI patients aged 52 (44; 58) years. A two-dimensional echocardiography was performed with the analysis of standard parameters and STE with an analysis of strain and rotational characteristics of the myocardium. In addition, brain natriuretic peptide and troponin-I concentration was determined. The development of pathological post-infarction remodeling within 12-month follow-up was assessed as an end point. Depending on the outcome, 2 groups were formed: group 1 — patients with pathological remodeling (PR), n=45 (39,5%), group 2 — patients without PR, n=69 (60,5%).Results. Early remodeling was detected in 24 (53,3%) people, mid-term — in 15 (33,4%), and late remodeling — in 6 (13,3%). In the PR group, heart failure (HF) was detected in 100% of patients, while in non-PR group, 23 (33,3%) patients had no signs of HF.In the early period of myocardial infarction, each of following indicators with high sensitivity and specificity predicts postinfarction pathological dilatation: global longitudinal strain (GLS) <11,7%, global circular strain (GCS) <12,4%, and a Twist decrease to 7,8o. A multivariate logistic regression model was created for the formation of pathological remodeling in patients with STEMI, which included GLS, global radial deformation (GRS), end-systolic volume index (ESVI), determined on days 7-9 of STEMI.Conclusion. GLS, GCS, and left ventricular Twist are independent highly sensitive and specific predictors of pathological remodeling. The following early predictors of postinfarction pathological dilatation have been established: reduced GLS  in combination with higher GRS and left ventricular ESVI.